The risk–gang nexus in Sweden: Penal layering and the uneven topography of penal change - Örnlind, Henrik (Punishment & society, 2023)
This article maps the emergence of a risk–gang nexus in the Swedish correctional field. Using the concept of penal layering, the article analyses the configuration of risk-based practices to manage gang affiliates in the context of Swedish prison and probation services. By introducing the notion interludes of penal layering, this article stresses the synchronic/diachronic opposition in penal change processes and furthers ongoing discussions of the variegated, braided, and uneven patterns of penal change in and beyond Nordic penal institutions. Drawing on interviews with probation officers, prison staff, and other professionals working with gangs in Sweden, the study finds that new rules, practices, decisional hierarchies, and actors have been layered on top of or alongside existing institutional arrangements to manage gang affiliates. This penal layer enforces punitive conditions for incarcerated gang affiliates and creates tensions, agonism, and contradictions between the coexisting and multiple logics of rehabilitation, punishment, and risk in the penal field.